A note on calculating expected shortfall for discrete time stochastic volatility models - Michael Grabchak; Eliana Christou (Financial Innovation, 2021)
In this paper we consider the problem of estimating expected shortfall (ES) for discrete time stochastic volatility (SV) models. Specifically, we develop Monte Carlo methods to evaluate ES for a variety of commonly used SV models. This includes both models where the innovations are independent of the volatility and where there is dependence. This dependence aims to capture the well-known leverage effect. The performance of our Monte Carlo methods is analyzed through simulations and empirical analyses of four major US indices.
Keywords: 650; Expected shortfall; Stochastic volatility; Value-at-risk